Antimicrobial usage at a large teaching hospital in Lusaka, Zambia - Masich, Anne M. (PLoS One, 2020)
Antimicrobial resistance is a growing global health concern. Antimicrobial stewardship (AMS) curbs resistance rates by encouraging rational antimicrobial use. However, data on antimicrobial stewardship in developing countries is scarce. The objective of this study was to characterize antimicrobial use at the University Teaching Hospital (UTH) in Lusaka, Zambia as a guiding step in the development of an AMS program. This was a cross-sectional, observational study evaluating antimicrobial appropriateness and consumption in non-critically ill adult medicine patients admitted to UTH. Appropriateness was defined as a composite measure based upon daily chart review. Sixty percent (88/146) of all adult patients admitted to the general wards had at least one antimicrobial ordered and were included in this study. The most commonly treated infectious diseases were tuberculosis, pneumonia, and septicemia. Treatment of drug sensitive tuberculosis is standardized in a four-drug combination pill of rifampicin, isoniazid, pyrazinamide and ethambutol, therefore appropriateness of therapy was not further evaluated. The most common antimicrobials ordered were cefotaxime (n = 45), ceftriaxone (n = 28), and metronidazole (n = 14). Overall, 67% of antimicrobial orders were inappropriately prescribed to some extent, largely driven by incorrect dose or frequency in patients with renal dysfunction. Antimicrobial prescribing among hospitalized patients at UTH is common and there is room for optimization of a majority of antimicrobial orders. Availability of certain antimicrobials must be taken into consideration during AMS program development.